Gaya Manajemen Konflik Dalam Keluarga Pada Pasangan Suami Istri Yang Bekerja Di Kabupaten Lumajang - Mahmudah, Annisa’ul; Ridho, Muhammad Iqbal; Muksinin, Imam; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2023)
In a family, communication between husband and wife is very important to resolve various conflicts that occur in the family. Disturbance in the family, namely the presence of conflict when a wife has multiple roles. This study aims to determine the style of conflict management in the family of married couples working in Lumajang district. This research uses descriptive qualitative research methods with observational data collection techniques for married couples who work . The sampling technique in this study used a random sampling technique/probability sampling. Subjects who became a research sample with criteria were married couples, especially wives who work and live in Lumajang Regency. The results of this study are conflict management styles in the household in married couples who work in Lumajang Regency have various styles of conflict management.